(untitled) (Journal of Statistical Research, 2024)
Assuming binary treatment outcomes, a covariate adjusted response adaptive (CARA) design is developed for multi-arm clinical trials assuming the presence of treatment-covariate interaction. The proposed allocation skews the allocation dynamically according to the performance of the treatments and the covariate profile of any incoming subject. Relevant de- sign and precision based measures of the performance are further investigated empirically, which established the usefulness of the proposed allocation design over its competitors. Journal of Statistical Research 2023, Vol. 57, No. 1-2, pp.21-33